TECHNICAL EFFICIENCY OF VEGETABLE PRODUCTION AMONG WETLAND VEGETABLE FARMERS IN SOUTHWEST NIGERIA - BOLARINWA, Oluwaseun; O.O, Olubanjo; A.O, Otunaiya; A.O, Idowu (BADEGGI JOURNAL OF AGRICULTURAL RESEARCH AND ENVIRONMENT, 2024)
This study employed Cobb-Douglas Stochastic Frontier Production function to measure technical efficiency and its determinants among dry season vegetable farmers in selected wetland catchments in Southwest Nigeria. A multistage random sampling procedure was adopted to select 450 wetlands vegetable farmers across Oyo, Ogun and Lagos States and data were collected with the aid of structured questionnaire in 2020. Technical efficiency (TE) estimates indicated that wetlands vegetable farmers operated below the production frontier with the mean technical efficiency value of 0.74. Increased farm size, family labour, quantity of seed planted, and quantity of agrochemical significantly (p<0.01) improved the farmers’ technical efficiency level. The study found that extension contact, access to credit, farming experience, and membership of an association negatively and significantly related to technical inefficiency at 1 and 5%. Weighted average price and household size were significantly and positively related to technical inefficiency. It was recommended that attention should be given to improvement in the visitation by extension agent, the provision of improved seeds and affordable financial support. Key words: Efficiency, Stochastic frontier, Vegetable, Wetland,